El alcohol y su efecto en la salud de los adolescentes de la Unidad Educativa Monseñor Santiago Fernández García - Vásquez Jimbo, Dora Lucía (2015)
Alcohol affects almost all organs, especially the gastrointestinal, cardiovascular, central nervous and peripheral systems; also with the ingesting of alcohol some disorders occur like metabolic, nutritional, and it impacts the autoimmune system. It is relevant to remember that alcohol is the third leading risk factor for disease and accidents around the world, such as: cancer, violence, liver damage, pancreatitis, cirrhosis, mouth and pharynx cancer, neurological problems and mental illnesses that are intensified, such as epilepsy, depression or anxiety. No doubt the influence of alcohol in teenagers also encourage to aggressive behavior, because they reduce fear, increase their anxiety and push their actions to make risky and violent actions. Locally, among the most common diseases affecting the town of Loja because of alcohol consumption, there are: renal failure, hypertension, congestive heart failure, and even fractures. Those are the reasons why this research was carried, and it is entitled ALCOHOL AND ITS EFFECTS ON ADOLESCENTS’ HEALTH IN UNIDAD EDUCATIVA “MONSEÑOR SANTIAGO FERNANDEZ GARCÍA”, the objectives of the research were the following: To know the side effects alcohol causes on the health of adolescents. Through descriptive and quantitative studies, based on a total sample of 144 teenagers. The research showed the following conclusions: 100% consume alcohol, their health is mainly affected the central nervous system; the 72.22% it affects balance, 70.13% were facing headaches and a 71.52% lost their appetite. KEY WORDS: alcohol, health effects, teenagers.